Answer:
8 1/6
Step-by-step explanation:
that is da answer bbbbb
Answer:
-4, -6, -3, -5, -1. The inequality solved for n is n ≥ -6.
Step-by-step explanation:
Substitute all the values in the equation.
n/2 ≥ -3
-10/2 ≥ -3
-5 is not ≥ -3.
n/2 ≥ -3
-7/2 ≥ -3
-3.5 is not ≥ -3.
n/2 ≥ -3
-4/2 ≥ -3
-2 is ≥ -3.
n/2 ≥ -3
-9/2 ≥ -3
-4.5 is not ≥ -3.
n/2 ≥ -3
-6/2 ≥ -3
-3 is ≥ -3.
n/2 ≥ -3
-3/2 ≥ -3
-1.5 is ≥ -3.
n/2 ≥ -3
-8/2 ≥ -3
-4 is not ≥ -3.
n/2 ≥ -3
-5/2 ≥ -3
-2.5 is ≥ -3.
n/2 ≥ -3
-2/2 ≥ -3
-1 is ≥ -3.
To solve the inequality n/2 ≥ -3 for n, do these steps.
n/2 ≥ -3
Multiply by 2.
n ≥ -6.
The answer is c. forgive me if i am wrong
Answer:
Step-by-step explanation:
1,248
Answer:
The answer is A
Step-by-step explanation:
f(x) = x+2
g(x) = x²
g(fx) = (x+2)²
= x²+4x+4
g(fx)(-5) = (-5)²+4(-5)+4
= 25 - 20 + 4
= 9